HIERARKI PUSAT PELAYANAN DI KECAMATAN UNGARAN BARAT DAN UNGARAN TIMUR KABUPATEN SEMARANG - Hardati, Puji (Jurnal Geografi, 2016)
The study aims to identify the hierarchy of service centers. The unit of analysis is the village/ward insubdistricts of West and East Ungaran. The variables used were the infrastructure and facilities in 21villages/wards. Descriptive analysis using percentages, tables, and indexes. In Subdistrict East Ungaran allvillages/wards into the hierarchy of three, with the highest index value in the ward Kalirejo, while in theSubdistrict of West Ungaran, there are two villages included in the hierarchy of the two, with the highestindex value in the ward Bandarjo. West Ungaran subdistrict is a region having a population of at most andhighest density. Village of Bandarjo into a service center activities of the population. Its territory is near thehighway Semarang-Surakarta/Yogyakarta, have hight accessibility.